Modeling for managing geographical data movement - Mohd. Rahim, Mohd. Shafry (2005)
NARGIS – the North Australian Remote Sensing and GIS forum came into being in 1993. Since then conferences have been held biannually in the Northern Territory and Queensland. Over the last decade great technological advancements have been made in the spatial sciences. As NARGIS goes into the next decade of existence, the spatial sciences are set to evolve even further.